Digitalisation in accounting - D. V. Gileva (Вестник университета)
The aim of the article is to identify the problems encountered in the digitalisation process in accounting, consider ways of implementing digital transformation, and proposals to improve the enterprise’s accounting apparatus quality and efficiency. In accordance with this aim, the following research objectives have been defined: to justify the need to introduce digitalisation in the accounting field, determine key digital technologies, identify the transformation problems and advantages. In the course of the study, ways to solve urgent problems have been proposed, such as planning for digital transformation and the qualified employees lack in this field. The scientific novelty of this article lies in the prerequisites for the digital technologies introduction into the enterprise accounting department. As the results of the study, the need to compile competencies in digital technologies and introduce digitalisation into accounting has been identified. The main conclusion of the article is the necessity to digitalise the accounting aspect in order to generate reliable data on a company’s financial position.